2019
DOI: 10.1016/j.dhjo.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

“Stop bullying now!” Investigating the effectiveness of a serious game for teachers in promoting autonomy-supporting strategies for disabled adults: A randomized controlled trial

Abstract: Background: Individuals with disabilities are at heightened risk for bullying and can lack the ability to cope in bullying situations. Teachers and caregivers have an important responsibility to promote optimal strategies for individuals with disabilities to cope with bullying. Three types of strategies have been identified: autonomy-supporting, autonomy-neutral, and autonomy-undermining strategies. Objectives: The current study investigates the effectiveness of a serious game, "Stop bullying now!", for teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, games, digital games, educational games, and video games, together, are the second most used set of author keywords. It can be inferred from this finding that the term "serious game" has been used in the majority of articles, especially in recent years (Bang et al, 2019;Faria et al, 2019;García-Redondo et al, 2019;Jaramillo-Alcázar et al, 2020;Lievense et al, 2019;Ronimus et al, 2020;Tang et al, 2019). Based on the bibliometric results, disability and rehabilitation are also among the most used author keywords.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, games, digital games, educational games, and video games, together, are the second most used set of author keywords. It can be inferred from this finding that the term "serious game" has been used in the majority of articles, especially in recent years (Bang et al, 2019;Faria et al, 2019;García-Redondo et al, 2019;Jaramillo-Alcázar et al, 2020;Lievense et al, 2019;Ronimus et al, 2020;Tang et al, 2019). Based on the bibliometric results, disability and rehabilitation are also among the most used author keywords.…”
Section: Discussionmentioning
confidence: 96%
“…Since those are an important aspect of development among adolescents and are often experienced differently among adolescents with a visual impairment (Kef & Bos, 2006), further research is encouraged. Bullying (Lievense et al, 2019; Pinquart, 2017), stigma and discrimination (Green et al, 2005) should likewise gain more attention in future research since individuals with a disability are at risk of experiencing such adversities and being less able to cope with them (Brunes et al, 2018), and few studies on these topics were found in children with a visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the nature of care that individuals with ID receive can significantly impinge on their autonomy and, subsequently, their psychological well-being and self-worth (Petner-Arrey & Copeland 2015; Salt & Jahoda 2020; Wehmeyer 2020). Thus, it takes great attention to design in a care plan that identifies the unique needs and capacities of each client and provides adequate support while promoting autonomy (Deci & Ryan 2002;Lievense et al 2019).…”
Section: Introductionmentioning
confidence: 99%